FINITE ELEMENT MODELLING OF A TURBINE BLADE TO STUDY THE EFFECT OF MULTIPLE CRACKS USING MODAL PARAMETERS - RAVI PRAKASH BABU KOCHARLA; RAGHU KUMAR BANDLAM; MALLIKARJUNA RAO KUCHIBOTLA (Journal of Engineering Science and Technology, 2016)
The presence of crack in a structure tends to modify its modal parameters (natural frequencies and mode shapes). The fact can be used inversely to predict the crack parameters (crack depth and its location) from measurement of the changes in the modal parameters, once a functional relationship between them has been established. The machine components like turbine blade can be treated as a cantilever beam. Vibration analysis of cantilever beam can be extended successfully to develop online crack detection methodology in turbine blade. In the present work, finite element model of a cantilever beam for flexural vibrations has been considered by including two transverse open U-notches. The modal analysis has been carried out on cantilever beam with two U-notches and observed the influence of one U-notch on the other for natural frequencies and mode shapes. It is found that a certain frequency may correspond to different crack depths and locations. Later, by using a central difference approximation, curvature mode shapes were then calculated from the displacement mode shapes. The location and depth corresponding to any peak on this curve becomes a possible notch location and depth. The identification procedure presented in this study is a useful tool for detection of multiple cracks in a turbine blade.